Propuesta de los procedimientos técnicos según la Norma ISO 17025:2005 para la Evaluación de la Calidad Fisicoquímica y Microbiológica de la Leche en el Laboratorio de Análisis de Alimentos y Aguas de la Municipalidad Provincial de Trujillo - Arística Luna, Fabiola Yamali (2017)
The present investigation work consists on the development of a proposal of the technical procedures according to the technical requirements of the norm ISO 17025:2005 for the physiochemical analysis of the milk in the tests of acidity determination and determination of fatty matter and for the analysis microbiological of milk in the test of coliform determination, in the Laboratory of Analysis of Food and Water of the Provincial Municipality of Trujillo. As a result, it was described the mission, vision, politics of quality, objectives of quality, the reach of the service of tests and the flowchart of the Laboratory; to know the strategic guidelines, the wallet of services and the structure of the organization in study. The diagnosis was made and it was determined that the grade of execution of the technical requirements of the norm ISO 17025:2005 were of 3,4%; this way the current state of the laboratory was identified regarding the evaluated requirements. It has been proposed political, procedures, formats, specifications, descriptions of work position, support documents, among other activities, according to the technical requirements of the norm ISO 17025:2005 that it will allow to the Laboratory to demonstrate technical competition and to guarantee results of tests technically valid by means of their implementation.